Investigation of discontinuous precipitation upon age-hardening of invar-based Sn alloy. Issue 20 (18th September 2017) - Akhlaghi, Maryam; Rahimi, Reza; Schröder, Christina; Fabrichnaya, Olga; Volkova, Olena
Abstract: Abstract : Age-hardening of homogenized and cold-rolled invar-based Sn alloys results in the development of continuously-formed (CP) and discontinuously-formed (DP) Ni3 Sn2 precipitates. In situ investigation of the DP reaction front (RF) velocity ( V ) revealed a nonsteady-state behavior upon early aging stages followed by a constant V after prolonged aging. The reason for the initial nonsteady-state behavior was experimentally studied and attributed to the reduction of matrix Sn-supersaturation ahead of the DP RF as a result of the simultaneous CP coarsening (in homogenized specimen) or the CP increased volume fraction (in cold-rolled specimen). A similar trend of V variation in the homogenized specimen was obtained after the modification of the original Hornbogen model for the nonsteady-state DP growth kinetics. In general, variations of the transformed matrix fraction via the DP reaction suggest the faster kinetics of this reaction in cold-rolled specimen as compared to the homogenized one due to the existence of more nucleation sites induced by the cold deformation.